Improving sepsis screening and care in a developing nation health setting: A description of implementation. (3rd November 2021) - Alberto, Laura; Marshall, Andrea P.; Walker, Rachel M.; Pálizas, Fernando; Aitken, Leanne M.
Abstract: Evidence on sepsis screening and care in developing nations is insufficient to inform implementation practices in hospital wards. The aim of this multi‐method study was to describe and evaluate the implementation of a three‐step intervention (sepsis screening, alert activation, care) in five wards in Argentina in 2017. The implementation involved three stages: (1) context assessment, (2) development/participation in implementation strategies, and (3) evaluation of intervention adherence. Results were variable. The context assessment (Stage 1) demonstrated the value of education, proactivity towards care and team structures. Strategies developed (Stage 2) included sepsis screening and response guide, education, team rounding, posters, champions, audit/feedback and knowledge brokering. In Stage 3, staff screened 92% patients (506/547) for sepsis at ≥60% of set times; only 33% (21/64) patients had a sepsis alert activated when needed. A similar proportion of patients who had alerts activated ( n = 16, 76%) or not ( n = 32, 74%) received at least one element of care. The use of implementation strategies resulted in adherence to some aspects of the intervention. Future research is needed to improve sepsis screening and alert activation and care in this setting.